Royal College of Pathologists' United Kingdom pilot study of laboratory accreditation. The College Accreditation Steering Committee. (1990)
The Royal College of Pathologists recently commissioned a pilot study to assess the feasibility, desirability, and cost of establishing a national scheme for laboratory accreditation in the United Kingdom. Using a format similar to that designed by the College of American Pathologists, eight inspectors visited 24 laboratories comprising the major disciplines of two district hospitals, two teaching hospitals, a specialised (paediatric) hospital and a private hospital. Nine were considered accreditable without reservation, but 15 had deficiencies identified of differing importance which needed to be corrected before accreditation could be awarded. Problems identified were variable, but none related to technical performance and many did not require extra resources to correct. The exercise was conducted without organisational difficulty at an approximate direct cost of 300 pounds per laboratory. The study shows that the format used could form the basis of a cost effective nationwide strategy. The type of problems identified suggest that such a strategy is more likely to succeed if it is organised from within the pathology professions.